Trends in Loss-Adjusted Availability of Added Sugars and Energy Contribution from Macronutrients and Major Food Groups in Canada and the United States. Issue 5 (4th July 2023) - Wang, Ye (Flora); Marsden, Sandra; Chiavaroli, Laura; DiAngelo, Chiara; Sievenpiper, John L.
Abstract: Objective: : A clear understanding of changes in the consumption of sugars and other sugars-containing foods has become essential for dietary recommendations and nutrition policy considerations. This study aimed to estimate the consumption trends of added sugars, energy, macronutrients, and food categories using food supply data. Methods: : Annual food availability data were obtained from Statistics Canada "Food Available in Canada" database and compared to the equivalent data from Canadian Community Health Survey 2004/2015 and USDA "Food Availability (Per Capita) Data System". Results: : There was a 17% decline in the loss-adjusted per capita consumption of added sugars (%energy) in Canada over the past two decades, largely attributed to reduced intakes of refined sugar and sugars from soft drinks. Added sugars consumption was generally 30% less than that in the US. There was also a consistent decline in total energy intake and %energy from carbohydrates, accompanied by increased %energy derived from fats particularly during the most recent 10 years. Conclusion: : The observed trends in added sugars availability are similar to findings from the Canadian Community Health Surveys, demonstrating the potential application of annual loss-adjusted food availability data in monitoring trends in food and macronutrient intakes over time to complement dietary survey data in informing public policy development.